Kaupungin paikat ja nimet: Tornion Suensaaren nimistö - Ainiala, Terhi (Virittäjä, 2004)
Urban place names: The Suensaari district of Tornio (englanti) 1/2004 (108) Urban place names: The Suensaari district of Tornio The article examines place names in the Suensaari district of central Tornio, a town in northern Finland. The study forms part of a larger research project on urban names, focusing on their composition and fundamental nature. The survey of place names in Suensaari is the first precise quantitative analysis of the place names of an urban district. The study material was gathered from interviews and using written questionnaires. The material collected contains a total of 260 names covering 166 different places. A little over half of the places are buildings. If all the official and unofficial variants of the 260 place names are included, the total comes to 428 names. Variants of building names account for as much as two thirds of this total. Unofficial names make up 63 per cent of all the name variants. Almost all the places had unofficial name variants in addition to their official names. For some places, however, such as important nature sites and parks, the official names were clearly more common than the unofficial ones. The writer presents the best-known places and names in Suensaari and considers why some of the principal places have no unofficial variant of their name. The unofficial nomenclature is analysed and divided into secondary names (formed on the basis of an official name) and primary names (describing the place in some way or another). Some names included features of both categories. The writer also takes a look at knowledge of place names, comparing the knowledge of people born in the area and those who have moved there from elsewhere. The least used of the official names in Suensaari are the street names. These are rarely used, their use being confined to special situations. Instead of using street names, places are referred to according to the names of suburbs, neighbourhoods and key buildings. Attitudes towards multiple naming schemes that apply a particular subject theme were also examined: in general, people had a positive attitude towards such names. Terhi Ainiala